Effect of Concentrate Mixture Containing Varying Levels of Crude Protein on Growth Performance, Serum Biochemical Profile of Punganur Calves - Kavya, A; Reddy, G Nagi; Ravi, A; Raju, G Ganga; Suryanarayana, M V A N (Indian Journal of Animal Nutrition, 2025)
A study was conducted to arrive at the optimum CP content of concentrate mixture for growing Punganur calves based on their growth performance, nutrient digestibility, serum biochemical profile and hormonal status. In a completely randomized design, fifteen growing Punganur calves of 3-4 months of age with average body weight of 29.72±2.96 kg were selected randomly and divided into three homogenous groups with five calves per treatment and fed on Super napier grass adlibitum supplemented with concentrate mixture containing 14 (T1), 16 (T2) and 18% (T3) CP at 1% live weight. The experiment lasted for 90 days. The weight gain (kg) was 20.80, 20.76 and 21.17 in T1, T2 and T3, and the corresponding average daily gain (g) was 233.71, 233.26 and 237.95 in T1, T2 and T3, respectively and was not significantly different among treatments. There was no significant difference in total DMI (g), DMI/kg gain, nutrient digestibility, haematological, serum biochemical constituents, growth hormone, IGF-1, T3 and T4 among the treatment groups. The results of the current study indicated that the concentrate mixture with 14% CP on Super Napier based diet was optimum for Punganur calves.